If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x + 59) + (6x + -6) + (3x + 8) + (12x + 29) = 360 Reorder the terms: (59 + 9x) + (6x + -6) + (3x + 8) + (12x + 29) = 360 Remove parenthesis around (59 + 9x) 59 + 9x + (6x + -6) + (3x + 8) + (12x + 29) = 360 Reorder the terms: 59 + 9x + (-6 + 6x) + (3x + 8) + (12x + 29) = 360 Remove parenthesis around (-6 + 6x) 59 + 9x + -6 + 6x + (3x + 8) + (12x + 29) = 360 Reorder the terms: 59 + 9x + -6 + 6x + (8 + 3x) + (12x + 29) = 360 Remove parenthesis around (8 + 3x) 59 + 9x + -6 + 6x + 8 + 3x + (12x + 29) = 360 Reorder the terms: 59 + 9x + -6 + 6x + 8 + 3x + (29 + 12x) = 360 Remove parenthesis around (29 + 12x) 59 + 9x + -6 + 6x + 8 + 3x + 29 + 12x = 360 Reorder the terms: 59 + -6 + 8 + 29 + 9x + 6x + 3x + 12x = 360 Combine like terms: 59 + -6 = 53 53 + 8 + 29 + 9x + 6x + 3x + 12x = 360 Combine like terms: 53 + 8 = 61 61 + 29 + 9x + 6x + 3x + 12x = 360 Combine like terms: 61 + 29 = 90 90 + 9x + 6x + 3x + 12x = 360 Combine like terms: 9x + 6x = 15x 90 + 15x + 3x + 12x = 360 Combine like terms: 15x + 3x = 18x 90 + 18x + 12x = 360 Combine like terms: 18x + 12x = 30x 90 + 30x = 360 Solving 90 + 30x = 360 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-90' to each side of the equation. 90 + -90 + 30x = 360 + -90 Combine like terms: 90 + -90 = 0 0 + 30x = 360 + -90 30x = 360 + -90 Combine like terms: 360 + -90 = 270 30x = 270 Divide each side by '30'. x = 9 Simplifying x = 9
| /8+/50+2/2= | | 162=-8x+10 | | -7(p+1)+3=-18-5p | | -4u+4u-9= | | 28x-7=26 | | -6x^2+54x-48=0 | | 8+x=x-1 | | -3u-8u= | | t-81+50=-7 | | 3(3x-6)+4(-5x-1)=-8 | | 13+x=47 | | 4x-6-5x+5=x-4 | | -10n+12=-6n-16 | | -4(2x+3)=-8x-12 | | 8u^2+10u^2= | | 8(3x-6)+4(-5x-1)=-8- | | 36a^4+108a^3+77a-12a-9= | | 2x+8-20=-3x-(-18) | | x+(x+1)+(x+2)+(x+3)=26 | | (4x+8)+(9x-43)+(8x+9)+(5x+48)=360 | | -19+11x=9+10x | | x+6-2x=15 | | (5a)-1+a=11 | | 2(2x-10)=4(x-10) | | X-3(2x-3)+15=9 | | -64+100= | | -3+5m-5+2m=6m+4 | | -8+2x=-8 | | 10X-6X-10=6 | | 9(1-x)=-63 | | -23+5x=-23 | | -4a+9+4a= |